Community use of school grounds outside of school hours - Lin E-Y; Witten K; Carroll P; Parker K (Taylor and Francis Group, 2024)
Physical activity in childhood is essential for healthy development and wellbeing and school grounds can provide neighbourhood access to safe play spaces. This study examines the relationship between school demographics (school size, school decile, ethnicity of students and population density) and whether school grounds are open or closed for community use outside school hours. Data were gathered from 391 primary and intermediate schools across Tāmaki Makaurau (Auckland), Aotearoa New Zealand (84% of Auckland schools) with 250 schools participating in the full survey. The results indicate that higher school decile and lower population density are associated with school grounds being available for community use. This result is concerning. With closed school grounds more likely to be in lower socio-economic and higher population density areas, the children most affected are the same group who have fewer opportunities and less spaces for active play. The main reason schools closed their grounds was ‘vandalism /graffiti/theft concerns’. Low decile schools whose grounds were open outside of school hours shared a similar commitment to involve their communities widely in school activities and found doing so decreased the levels of vandalism. Their approach may offer useful insights to schools that are currently closed.
Keywords: school ground; community use; children; play; socioeconomic status